Hubungan Tingkat Konsumsi Protein dan Vitamin A Terhadap Perubahan BTA TB Paru Setelah Pengobatan Fase Intensif di RS Paru Jember - Ayu Fitriana; Agustina Endah Werdiharini (Politeknik Negeri Jember, 2022)
Tuberculosis is a contagious disease caused by Mycobacterium tuberculosis. The newest cases of pulmonary TB cases in Indonesia year 2018 is 203,348 cases with positive bacteriological results. The failure to change positive BTA sputum to negative BTA is caused by the deficiency of nutrients that are protein and vitamin A. The deficiency of nutrients in protein and vitamin A effect the decreasing the number of T lymphocyte cells so that bacteria remain alive in the lung tissue and the change in sputum positive BTA to BTA negative becomes slow. It could retard the patient's healing process. According to the description below, T lymphocytes could be increased by consumption of protein and vitamin A. The purpose of this study was to determine the relationship of Level of Protein and Vitamin A Intake with BTA TB Lung Conversion After Intensive Phase Treatment in RS Paru Jembe. The type of this research is observational with cross sectional design. The subject for this study was 38 TB patients who had intensive phase treatment. The data collection techniques were carried out through interviews using the SQ-FFQ and Fisher Exact forms used for data analysis. The results showed that there was a significant relationship between the level of protein consumption on the changes in BTA (p: 0.001) and there was no relationship the level of vitamin A consumption on the changes in BTA (p: 0.144).